2019
DOI: 10.1002/dev.21829
|View full text |Cite
|
Sign up to set email alerts
|

Day‐to‐day friends’ victimization, aggression perpetration, and morning cortisol activity in late adolescents

Abstract: This study investigates bidirectional associations between adolescents’ daily experiences of victimization and aggression perpetration within friendships. We investigated (a) across‐day associations between victimization and aggression perpetration; (b) morning cortisol activity as a moderator of cross‐day victimization and aggression links; and (c) potential sex differences in these patterns. For 4 consecutive days, 99 adolescents (Mage = 18.06, SD = 1.09, 46 females) reported whether they were victimized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…The majority of these studies included adolescents from community samples in midto-late adolescence, with roughly equal numbers of boys and girls. These studies found negative associations with either general measures of aggression (such as with the Youth Self Report; Grotzinger et al, 2018; Platje, Jansen, et al, 2013; Platje, Vermeiren, et al, 2013; Platje, Popma, et al, 2015; Yu et al, 2016) or with physical aggression (Johnson et al, 2014; Yu et al, 2019), while Arbel et al (2019) found a negative association with aggression directed toward friends which included physical, relational, and digital aggression. Finally, in two of these studies testosterone was considered in the relation between cortisol and aggression: Grotzinger et al (2018) found that low cortisol related to higher levels of aggression under high levels of testosterone only, and Platje et al (2015) found that high testosterone relative to cortisol related to higher levels of general aggression.…”
Section: Study Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of these studies included adolescents from community samples in midto-late adolescence, with roughly equal numbers of boys and girls. These studies found negative associations with either general measures of aggression (such as with the Youth Self Report; Grotzinger et al, 2018; Platje, Jansen, et al, 2013; Platje, Vermeiren, et al, 2013; Platje, Popma, et al, 2015; Yu et al, 2016) or with physical aggression (Johnson et al, 2014; Yu et al, 2019), while Arbel et al (2019) found a negative association with aggression directed toward friends which included physical, relational, and digital aggression. Finally, in two of these studies testosterone was considered in the relation between cortisol and aggression: Grotzinger et al (2018) found that low cortisol related to higher levels of aggression under high levels of testosterone only, and Platje et al (2015) found that high testosterone relative to cortisol related to higher levels of general aggression.…”
Section: Study Findingsmentioning
confidence: 99%
“…Eleven studies tested the relation between basal cortisol (afternoon levels or CAR) and aggression. Of these, nine studies report a negative association, indicating that lower levels of cortisol or a lower CAR relate to higher levels of aggression (Arbel et al, 2019; Grotzinger et al, 2018; M. M. Johnson et al, 2014; Kimonis et al, 2017; Platje, Jansen, et al, 2013; Platje et al, 2015; Platje, Vermeiren, et al, 2013; Yu et al, 2016, 2019), but note that the Platje et al and Yu et al studies include the same longitudinal community sample. One study examined a sample of adolescent detained boys (Kimonis et al, 2017); finding that higher levels of cortisol related to lower levels of overt aggression.…”
Section: Study Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to peer victimization, Arbel et al. ( 76 ) observed a positive association with peer aggression for both males and females, along with the finding that in male adolescents, this association was bi-directional. Furthermore, Babarro et al.…”
Section: Introductionmentioning
confidence: 98%